WORK CULTURE RECONSTRUCTION: AN ANALYSIS OF THE SHARIAH APPROACH - Ahmad Maulidizen (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2019)
There are three economic systems that apply in this world, namely those originating from the product of human reason (science) and which come from revelation. From the first source a secular capitalist and socialist system was born, while the second one was born a sharia-based economy. In reality, the secular system is unable to provide equitable prosperity, and it is not uncommon to even cause human tempest. In this case what is considered capable of providing solutions is another revelation-based system. However, the sharia teachings originating from the revelation still need to be explored and cultivated so that the community will become more insightful, understanding, and finally able to apply. This research is library research. The data is extracted using the documentary method. The results showed that Qardhawi's thinking was purely based on revelation with muamalah, fiqh and moral approach. While Chapra tried to cover how conventional economic work practices and compare them with the Islamic system, while offering solutions, through scientific approaches and Islamic values. The relevance of both thoughts is to be able to provide Islamic values in the development of an economic spirituality